Linguistic realizations of personality and emotional polarity in Tan Twan Eng’s The Garden of Evening Mists: A systemic functional discourse analysis - Mi Chen (PLoS ONE, 2026)
This study examines how personality and emotion are linguistically realized in Tan Twan Eng’s The Garden of Evening Mists , drawing on the Big Five Model of Personality (BFM) and Systemic Functional Linguistics (SFL) to construct an integrated theoretical-qualitative framework for the analysis of character language in literary narrative. Emotional polarity is understood as the systematic orientation of affective meaning, positive, neutral, or negative, realized through lexicogrammatical choices at the interpersonal, ideational, and textual levels of language. Through close discourse analysis of selected passages, the study traces how patterns of modality, process type, and cohesion correspond to shifts in emotional polarity across three narrative phases: trauma recollection, apprenticeship in Yugiri, and reflective closure. The findings indicate that emotional polarity in the novel can be read as a form of psychological adaptation rather than static sentiment: negative polarity, realized through obligation modals and syntactic compression, reflects a high-Conscientiousness, high-Neuroticism configuration associated with trauma-related self-regulation; neutral polarity, marked by evaluative balance and descriptive cohesion, signals stabilized Conscientiousness and emerging Openness; positive polarity, expressed through relational processes and permissive modality, corresponds to increased Openness and diminished Neuroticism. The interpersonal dimensions of Agreeableness and Extraversion are realized at lower density but trace parallel arcs across the three phases, with Agreeableness providing the linguistic site at which the novel’s central thematic question of inherited hatred is settled. By integrating Big Five personality theory with systemic-functional analysis, the study offers a theoretically grounded and interpretively transparent framework for investigating how emotional language encodes personality transformation in narrative discourse. The findings contribute to ongoing dialogues between personality psychology, functional linguistics, and literary stylistics and illustrate how this framework can be applied to postcolonial narrative fiction.